Taxifolin, a novel food, attenuates acute alcohol-induced liver injury in mice through regulating the NF-κB-mediated inflammation and PI3K/Akt signalling pathways. (1st January 2021) - Ding, Chuanbo; Zhao, Yingchun; Chen, Xueyan; Zheng, Yinan; Liu, Wencong; Liu, Xinglong
Abstract: Context: Taxifolin (TAX) has effective anti-inflammatory, antioxidant and hepatoprotective activities, but its potential mechanism has not been revealed. Objective: To evaluate the potential protective effect of TAX on acute alcohol-induced liver injury in mice. Materials and methods: Alcoholic liver injury model was established by oral alcohol in mice, and randomly distributed in five groups ( n = 10): Normal group (oral saline only); Alcohol group (concentration of fermented alcohol: 56%, 6 mL/kg); TAX groups, mice were orally administered with alcohol, and then TAX with doses of 20, 40, 80 mg/kg, respectively. Oral administration was conducted for 6 weeks. Results: TAX treatment illustrated that the level of alanine aminotransferase (ALT) was reduced to 65.90 ± 2.26 U/L and aspartate aminotransferase (AST) to 33.28 ± 5.62 U/L compared with alcohol group (ALT 124.51 ± 4.40 U/L, AST 61.70 ± 4.09 U/L), while superoxide dismutase (SOD) was increased to 49.81 ± 2.39 U/mg and glutathione (GSH) to 8.16 ± 0.44 μmol/g, but MDA was reversed to 2.53 ± 0.24 nmol/mg. Histopathological examination showed TAX treatment alleviated alcohol-induced hepatocyte necrosis and inflammatory infiltration. Meanwhile, Western blot and rt-PCR indicated TAX reduced IL-6 to 2.49 ± 0.25 pg/mL and TNF-α to 1.79 ± 0.20 pg/mL, and inhibiting NF-κB activation in liver. Moreover, TAX reversed alcohol-induced apoptosis by regulating the expression of PI3K/Akt and its downstream apoptotic factors. Conclusions: The research provides novel evidence of the hepatoprotective effect of TAX on alcohol-induced liver injury, while also providing the possibility for future treatment of alcoholic liver disease.